How to choose proper local treatment in men aged ≥75 years with cT2 localized prostate cancer?. (8th May 2019) - Jin, Kun; Qiu, Shi; Li, Jiakun; Zheng, Xiaonan; Tu, Xiang; Liao, Xinyang; Yang, Yan; Yang, Lu; Wei, Qiang
Abstract: Background: For localized prostate cancer (PCa), radical prostatectomy (RP) and radiotherapy (RT) are two standard interventions to decrease PCa mortality. Contemporary studies contained the elderly people; analyses focusing on patients over 75 years of age were still lacking. Method: In the Surveillance Epidemiology and End Results (SEER) database (2004‐2015), people over 75 years of age with cT2 stage were selected in our research. Multivariable Cox proportional hazard models were used to analyze cancer‐specific mortality (CSM) and overall mortality (OM) after adjustment. The propensity score matching was performed to assume the randomization. An instrument variate (IVA) was used to calculate the unmeasured confounders. Results: Radical prostatectomy is superior to RT in OM and CSM after adjustment for covariates (HR = 0.54, 95% CI = 0.47‐0.62, P  < 0.001 and HR = 0.30, 95% CI = 0.20‐0.45, P  < 0.001, respectively). The cox model after matching indicated similar consequence (OM: HR = 0.53, 95% CI = 0.46‐0.62, P  < 0.001; CSM: HR = 0.27, 95% CI = 0.17‐0.43, P  < 0.001). In the IVA‐adjusted model, the effect of treatment changed slightly (OM: HR = 0.65, 95% CI = 0.54‐0.78, P  < 0.001; CSM: HR = 0.21, 95% CI = 0.12‐0.37, P  < 0.001). Subgroup analyses showed that for patients with GS = 7, those received RP obtained the highest risk decline for overall death (HR = 0.41, 95% CI = 0.32‐0.52); and for patients with younger age, those received RP obtained the highest risk decline for CSM (HR = 0.11, 95% CI = 0.01‐0.52). Conclusion: Patients over 75 years of age with cT2 stage will obtain more benefit from RP compared with RT, especially for patients with GS = 7 and younger age. Abstract : For localized prostate cancer (PCa), radical prostatectomy (RP) and radiotherapy (RT) are two standard interventions to decrease PCa mortality. Contemporary studies contained the elderly people; analyses focusing on patients over 75 years of age were still lacking. We used SEER database to perform analyses and showed that patients over 75 years of age with cT2 stage will obtain more benefit from RP compared with RT, especially for patients with GS = 7 and younger age.